Increased incidence with improved survival of gynecologic carcinosarcoma: A population-based study. (November 2021) - Salman, Lina; Brudner, Yana; Silverman, Barbara G.; Hallak, Mordechai; Bruchim, Ilan
Abstract: Objective: To evaluate trends in the incidence and survival of gynecologic carcinosarcoma over the last 35 years and to explore ethnic disparities. Study design: Using the Israeli National Cancer Registry database, all cases of gynecologic carcinosarcoma were included (1980–2014). Age at diagnosis, patient's ethnicity and anatomical site were extracted. Age-standardized incidence rates (ASRs) were calculated for 3 time periods (1980–1994, 1995–2004 and 2005–2014). Relative survival was calculated using the Pohar-Perme method. Results: Overall, 935 cases of gynecologic carcinosarcomas were diagnosed during 1980–2014. The most common gynecologic anatomical site was the uterus (83.4%). Most cases (66%) were diagnosed at ages 60–80, with median age of 69 years. There was a steady increase in ASRs from 5.6 to 8.2 per million women. Throughout 1980–1994 and 2005–2014, ASRs were significantly higher in the Jewish compared to the Arab population (5.8 vs. 3.1, p = 0.02 and 8.5 vs. 5.2, p = 0.002, respectively). Relative survival rates increased throughout the study period. No significant differences were noted in relative survival between the Jewish and Arab populations (p = 0.18). Conclusion: The incidence of gynecologic carcinosarcoma increased significantly from 1980 through 2014. Nevertheless, survival rates increased during this time, with no difference in survival between the Jewish and Arab populations.